DEVELOPMENT OF METHODOLOGIES TO ASSESS AUTONOMIC NERVOUS SYSTEM FUNCTIONING AND NEUROMODULATION FOR THE DIAGNOSIS AND TREATMENT OF COLONIC MOTILITY DISORDERS - Ali, M. Khawar (My University, 2022)
Although parasympathetic activity (PNS) is the primary driver and sympathetic activity (SNS) is a significant inhibitor of colonic propulsive activity, they are rarely measured, and hence, they almost play no role in diagnosing dysfunction or standard treatments for chronic conditions such as refractory constipation. We aimed to develop methodologies for the assessment of autonomic nervous system (ANS) activity, establish criteria for autonomic dysfunction, and study if stimulation of lumbar and sacral autonomic nerves using low-level laser therapy (LLLT) could affect the ANS and explore it as a potential treatment of autonomic dysfunction to restore colonic motility. By studying the active standing test and the table tilt test as a method to evoke activity in the ANS, we rejected LF power, SD1 and SD2 of Poincare plot, Pre-ejection-period (PEP), complex-correlation-measure (CCM) and detrended fluctuation analysis (DFA). Respiratory-Sinus-Arrhythmia (RSA), Root-Mean-Square-of-Successive-Differences (RMSSD) were selected for PNS activity, the Baevsky’s-Stress-Index (SI) was chosen for SNS activity, and SI/RSA and SI/RMSSD were introduced as a measure of autonomic balance. We explored high-resolution-colonic-manometry with concurrent electrocardiography to observe whether these parameters could be associated with ANS changes during colonic motor patterns. High-amplitude-propagating-pressure-waves were associated with a strong parasympathetic activity and decreased sympathetic activity. Comparing ANS reactivity of patients with severe motility disorders to controls in response to postural changes, we observed that most patients have low PNS and elevated SNS baseline activity and reactivity. This established a way to evaluate autonomic dysfunction in patients with colon motor disorders. A single session of LLLT using LED and laser light on the lumbar and sacral spine in 41 patients with chronic gastrointestinal motor dysfunction indicated that treatments with LED light followed by laser light significantly increased parasympathetic activity and decreased sympathetic nervous system activities. These results initiated a study into the effects of LLLT on restoring autonomic dysfunction in chronic refractory colonic motility disorders.
AUTONOMIC ASSESSMENT FOR GI DYSMOTILITY AND NEUROMODULATION
Keywords: Autonomic, Neuromodulation, Motility; Parasympathetic, Sympathetic